DESAIN DAN ANALISIS MEKANISME BENDUNG GERAK DENGAN RADIAL GATE UNTUK PENANGANAN BANJIR ROB - Dirga Asmara Putra; Henny Pratiwi Adi; Slamet Imam Wahyudi (Politeknik Negeri Semarang, 2022)
Tidal floods are high tides that occur excessively on the mainland. Radial gate weiris a door building that moves around in a cylindrical shape to regulate the waterlevel elevation. This study aims to determine the influence factor of the radial gatemovement weir mechanism, analyze the fluid mechanics of the radial gate duringtidal flooding. This research is experimental design research, namely, making aprototype design of the radial gate motion weir mechanism and analysis ofparameter data in the form of hydrostatic pressure, hydrodynamic pressure, criticalflow, and sub critical flow. The conclusion of this study is, the design is planned towork when: the automation system runs because the two proximity sensors touch the30 cm water level, activate the linear actuator to close the radial gate, the waterpump turns on and 15 cm opens the radial gate, the water pump stops. The results ofparameter data analysis: hydrostatic pressure of water level 30 cm = 32.0 N/m2,hydrodynamic pressure due to earthquake according to (DSI) in Cilacap = 0.1211tf/m2, BMKG SIG (III/Light)= 33,600 tf/m2, (IV/ Medium)= 96.075 tf/m2,(V/Weight)= 148.3125 tf/m2. Critical flow rate of water level is 15 cm = 0.0149m3/second, sub-critical flow rate is 0.0098 m3/second.